Determinants of Tax Aggressiveness with Corporate Governance as a Moderation Variable in Technology Sector Companies in Indonesia - Hikmah Amalia Ramadani; Tiara Pandansari; Ani Kusbandiyah; Ira Hapsari (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study examines how Corporate Social Responsibility (CSR) and Executive Character influence Tax Aggressiveness, and evaluates whether Corporate Governance moderates these relationships in technology companies listed on the IDX during 2020–2024. This study uses a quantitative approach with secondary data from the annual reports of technology companies listed on the IDX. Using purposive sampling, 117 panel observations from 28 companies were obtained. The analysis was conducted using Moderated Regression Analysis (MRA) with SPSS 27 to test both direct and interaction effects. Classical assumption tests were also carried out to ensure the regression model validity. The results of this study found that CSR and Executive Character have a negative influence on tax aggressiveness. Corporate Governance, proxied by independent commissioners moderates the relationship but strengthens CSR and Executive Character on tax aggressiveness, indicating ineffective monitoring. The findings suggest that although CSR and executive character reduce tax aggressiveness, corporate governance mechanisms are not yet effective in overseeing tax related decisions. This implies that governance structures tend to function symbolically rather than substantively, highlighting the need for firms and regulators to strengthen the quality and effectiveness of tax supervision.